IMPLEMENTASI PRINSIP PARIWISATA BERBASIS KOMUNITAS DI DESA WISATA NGLINGGO YOGYAKARTA - Pakpahan, Rosdiana (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 01, July 2018, 2018)
This study is carried out in Nglinggo rural tourism destination located in Pagerharjo village, Samigaluh sub-district, Kulon Progo regency in Yogyakarta. This research is aimed at revealing the application CBT principles implemented in the management of the rural tourism attraction as well as finding supporting factors and obstacles on the application of the CBT principles. This study also traces why such factors and obstacles occur. This research applies both qualitative and quantitative techniques in obtaining primary and secondary data. The primary data is collected by questionnaires, in- depth interview and observation, while the secondary data is obtained mainly from local authority’s website of Office of Tourism of Kulon Progo Regency.This study suggests that local people are aware on the importance of involvement in managing their village as an attraction. Meanwhile, supporting factors of the application of CBT principles are natural resources, local people cohesion, contribution to local people, local community involvement, existence of supporting institution, management commitment, and local authority’s support. On the other hand, obstacle found in the application of the CBT principles are education and people readiness.